2015
DOI: 10.5539/ies.v8n13p41
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model to Implement Contextual Learning with Virtual Learning Environment for Promoting Higher Order Thinking Skills in Malaysian Secondary Schools

Abstract: One of the important features in developing science curriculum in Malaysia is the emphasis on the education system that allows students to master higher order thinking skills (HOTS). However, the current teaching practice tends to inhibit students' HOTS by which students are given drills and tutorials to perform better in examination. The contextual learning is deem as a suitable approach to develop HOTS, as it enables students to build their knowledge in the context of their minds, then later makes use of lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
1
12
0
5
Order By: Relevance
“…Waheed et al (2016) explored effects of Moodle Learning Management System on academic performance, intrinsic and extrinsic motivation in Pakistan, and found that blended learning has a positive impact on the mentioned variables. Importance of Virtual Learning Environment in Malaysian secondary science students was explained by Raub et al (2015) and found robust support to enhance higher order thinking skills. Similarly, Krasnova (2015) also demonstrated that integration of blended learning has contributed to increase quality of education in higher education in Russia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Waheed et al (2016) explored effects of Moodle Learning Management System on academic performance, intrinsic and extrinsic motivation in Pakistan, and found that blended learning has a positive impact on the mentioned variables. Importance of Virtual Learning Environment in Malaysian secondary science students was explained by Raub et al (2015) and found robust support to enhance higher order thinking skills. Similarly, Krasnova (2015) also demonstrated that integration of blended learning has contributed to increase quality of education in higher education in Russia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pada penelitian lain juga membuktikan bahwa model CTL juga dapat meningkatkan kemampuan berpikir kritis dan sikap ilmiah [12]. Model CTL juga dapat meningkatkan kemampuan berpikir tingkat tinggi siswa [13]. CTL adalah suatu prosedur pendidikan yang bertujuan untuk membantu siswa melihat makna dalam bahan pelajaran yang mereka pelajari dengan cara menghubungkannya dengan konteks kehidupan mereka sehari-hari yaitu dengan konteks lingkungan pribadinya, sosialnya, dan budanyanya [14].…”
Section: Penggunaan Model Contextual Teaching and Learning (Ctl)unclassified
“…The learning process using real life-oriented can facilitate the concept of thinking. Consequently, utilizing the environment as learning resources can improve the student's concept understanding (Istiani & Retnoningsih, 2015;Raub, Shukor, Arshad, & Rosli, 2015;Triyani, Putra, & Alimah, 2019). Besides, learning resources that are following the teaching materials can make it easier for students to construct their knowledge so that the concepts learned can produce long-term memory (Rufii, 2015;Schumm & Bogner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Students can face a real-life problem that exercises their senses to see and do so that learning is considered more interesting (Obergriesser & Stoeger, 2020). Thus, the use of the surrounding environment as learning resources can make it easier for students to remember concepts (Raub et al, 2015) and improve their emotional quotient and learning achievement (T.-C. Huang, Chen, & Chou, 2016) so that the learning becomes more meaningful.…”
Section: Introductionmentioning
confidence: 99%